Public Policies, Perceived Corruption and Transparency as Exogenous Antecedents of Entrepreneurship - Panagiota I. XANTHOPOULOU; Alexandros G. SAHINIDIS; Ioannis ANTONIADIS (Communications of International Proceedings, 2023)
Public sector worldwide faces the challenge to contribute in the public value creation. To accomplish that, public administration forced to adopt tools and practices from the private sector, such as “strategic management”, “performance measurement”, “customer focus, “innovation management”, and “public entrepreneurship” as best practices in order to improve social and economic welfare. The present research includes some of the most significant factors related to the external environment, focusing on national policies and on public administration related issues that impact on people’s entrepreneurial intention and on the development of entrepreneurship in general. The literature on a study topic was assessed, analyzed, and synthesized using the integrative or critical review approach in a way that promotes the formation of new theoretical frameworks and perspectives. The contribution of the study lies in two points, first this research approach is not common on the administration literature and secondly it adds more information from the current literature, and this could help researchers and policymakers to identify the key practices that will promote entrepreneurship. Findings showed that issues such as corruption, bad regulatory system, and the lack of public policies prevent individuals from being entrepreneurs, while other issues such as entrepreneurship education programs supported by governments, transparency, open governance and citizen’s trust are factors that boost innovation within a country and make individuals more optimistic to start their own business.
Keywords: Public sector; Public Government; Entrepreneurship; Entrepreneurial Intention; Corruption; Transparency